(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This paper investigates how gender is represented in Englishlanguage media discourse, focusing on both traditional and digital platforms such as news media, advertising, film, and social media. Using tools from critical discourse analysis and gender studies, the paper explores the linguistic and visual strategies used to construct masculinity and femininity, as well as how these representations influence societal perceptions, identity formation, and power relations. Special attention is given to stereotypes, language choices, framing, and the changing nature of gender portrayal in the age of social media and digital activism.